Metabolic profiling of genetic disorders: a multitissue (1)H nuclear magnetic resonance spectroscopic and pattern recognition study into dystrophic tissue. - Griffin, J; Williams, H; Sang, E; Clarke, K; Rae, C; Nicholson, J (2001)
A principal problem in understanding the functional genomics of a pathology is the wide-reaching biochemical effects that occur when the expression of a given protein is altered. To complement the information available to bioinformatics through genomic and proteomic approaches, a novel method of providing metabolite profiles for a disease is suggested, using pattern recognition coupled with (1)H NMR spectroscopy. Using this technique the mdx mouse, a model of Duchenne muscular dystrophy (DMD) was examined. Dystrophic tissue had distinct metabolic profiles not only for cardiac and other muscle tissues, but also in the cerebral cortex and cerebellum, where the role of dystrophin is still controversial. These metabolic ratios were expressed crudely as biomarker ratios to demonstrate the effectiveness of the approach at separating dystrophic from control tissue (cardiac (taurine/creatine): mdx = 2.08 +/- 0.04, control 1.55 +/- 0.04, P < 0.005; cortex (phosphocholine/taurine): mdx = 1.28 +/- 0.12, control = 0.83 +/- 0.05, P < 0.01; cerebellum (glutamate/creatine): mdx = 0.49 +/- 0.03, control = 0.34 +/- 0.03, P < 0.01). This technique produced new metabolic biomarkers for following disease progression but also demonstrated that many metabolic pathways are perturbed in dystrophic tissue.